2021
DOI: 10.1177/02724316211010332
|View full text |Cite
|
Sign up to set email alerts
|

Grade Retention and School Dropout: Comparing Specific Grade Levels Across Childhood and Early Adolescence

Abstract: Students who repeat a grade are at a higher risk of dropping out of high school. Previous research has examined this in a methodologically aggregated way (e.g., repeated any grade versus never repeated) or only specific grades/grade ranges (e.g., Kindergarten or elementary) leaving questions about which grades are more detrimental to repeat with respect to school dropout. This study uses data from the National Center for Education Statistics ( N = 9,309) to comparatively examine which grades, when repeated, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Therefore, grade retention speeds out the disengagement of pupils. The finding is in harmony with that by Giano et al (2022) which established that repeating students who were in the sixth or seventh grade had the utmost probability of disengaging from school. In other words, grade retention and school disengagement are positively correlated.…”
Section: Research Question 1: To What Extent Does Grade Retention Exi...supporting
confidence: 82%
“…Therefore, grade retention speeds out the disengagement of pupils. The finding is in harmony with that by Giano et al (2022) which established that repeating students who were in the sixth or seventh grade had the utmost probability of disengaging from school. In other words, grade retention and school disengagement are positively correlated.…”
Section: Research Question 1: To What Extent Does Grade Retention Exi...supporting
confidence: 82%
“…Sex differences have also been noted in school discipline outcomes, with boys reporting greater school suspensions (Camacho & Krezmien, 2019). Higher income has also been associated with better self-esteem (Bai et al, 2021), better school bonding (e.g., Assari, 2019), less grade retention (Giano et al, 2022), while lower income has been associated with greater suspensions (Camacho & Krezmien, 2019) and higher depression (Santiago et al, 2011). Finally, identity formation (e.g., self-esteem) has been found to change or increase across adolescent age (Meeus et al, 2010), and school connections and mental health have been found to worsen with age (e.g., Cavioni et al, 2021).…”
Section: Contextual and Demographic Influencesmentioning
confidence: 99%
“…Thus, we could not estimate the potential long-term effects of grade retention more precisely. Considering the specific grade when students were retained is important not only from a developmental perspective but also due to findings from previous studies, where grade retention effects differed according to the grade where they were retained, e.g., [66].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%